Strategi Advokasi Anti Diskriminasi sebagai Solusi Perlindungan terhadap Kelompok Rentan Albino - Mawadda, Nurul; Dewanti, Andi Putri; Alfarabi, Andi Ahmad; Aisyah, Nurul; Mubarak, Nurfitah Ersya; Andi Sapiddin, Andi Syahwiah (UNES Law Review, 2023)
In addressing the issue of discrimination against albino individuals, a specific and comprehensive approach and strategy are needed to prioritize human rights protection principles such as equality, equity, mutual respect, and inclusivity among individuals. This approach is known as "anti-discrimination advocacy." This research aims to examine the legal status of vulnerable albino groups, the fulfillment of albino individuals' human rights, and to design anti-discrimination advocacy strategies as a means of protection for the vulnerable albino community. This research utilizes a qualitative approach, combining normative-empirical research methods and in-depth interviews. Sample selection is conducted through purposive sampling techniques. The research findings indicate that albino individuals have not been explicitly recognized in legislation. The fulfillment of the human rights of albino individuals, especially in terms of physical and sensory limitations related to the right to life, education, health, and employment, remains suboptimal. Therefore, government involvement is necessary to ensure human rights protection for albino individuals, including their recognition in specific legislation, particularly in Law of the Republic of Indonesia No. 8 of 2016 on Persons with Disabilities.